Cutaneous Leishmaniasis vectors study at Rimac Valley - Tejada, Abelardo (2003)
Objectives: To determine the composition of Lutzomyia species at the Rimac valley. Material and methods: The area studied was the Ullupampa annex (2000 msnm), San Jeronimo de Surco district, Huarochiri province, Lima. The sandflies were captured using Shannon traps, CDC light traps and direct capture, in intra and peridomiciliary ambient and natural refuges. Results: We identified 1742 phlebotomine sandflies of the Lutzomyia genus, 52,6% corresponded to Lutzomyia verrucarum, 28,2% to Lutzomyia peruensis, and 19,2% to Lutzomyia noguchi; the first two were more abundant in intra and peridomiciliary ambients, and the latest in natural refuges. Lutzomyia density presents seasonal variations, mostly found between March and May. Night activity peak is between 20 and 21 hours. Conclusions: Fruit cultivations surrounded housings separated by “pircas” and domestic animals within the house favor L. peruensis and L. verrucarum hematophagous activity in the domiciliary ambient; they represent the main leishmaniasis vectors at Rimac valley.